Afomp policy statement No. 2: Recommended clinical radiation oncology medical physicist staffing levels in AFOMP countries - Round, W.H.; Tay, Y.K.; Ng, K.H.; Cheung, K.Y.; Fukuda, S.; Han, Y.; Huang, Y.X.; Kim, H.J.; Krisanachinda, A.; Liu, H.L. (Springer, 2010)
This document is the second of a series of policy statements being issued by the Asia-Oceania Federation of Organizations for Medical Physics (AFOMP). The document was developed by the AFOMP Professional Development Committee (PDC) and was released by the AFOMP Council in 2009. The main purpose of the document is to give guidance as to how many medical physicists are required to staff a radiation oncology department. Strict guidelines are difficult to define as work practices vary from country-to-country and from hospital-to-hospital. A calculation scheme is presented to aid in estimating medical physics staffing requirements that is primarily based on equipment levels and patient numbers but also with allowances for staff training, professional development and leave requirements.